Antidiabetic Potential of Vitex mombassae Fruits Extract in Streptozotocin-Nicotinamide Induced Diabetic Wistar Rat Model - Mbegeze, Mussa B.; Munissi, Joan J.E.; Stephano, Flora; Nondo, Ramadhani S.O.; Nyandoro, Stephen S. (Tanzania Journal of Science, 2023)
Besides changes in life styles and improper dietary patterns, the rapidly increasing burden of diabetes mellitus type 2 is correlated with antidiabetic agents currently in clinical use, which are costly, less effective, and present undesirable side effects. Natural products from plants are promising alternative sources for developing more effective and cost friendly antidiabetic agents. This study therefore investigated the antidiabetic potential of Vitex mombassae fruits extract (VMFE) in streptozotocin-nicotinamide induced diabetic Wistar rat model. Oral acute toxicity test was conducted in male Wistar rat using up and down method by following OECD Guideline 423 (2002). No clinical signs of toxicity were observed at 300 and 2000 mg/kg body weight (b.w.) doses used in the assays. The LD50 value was estimated to be ˃ 2000 mg/kg b.w. In evaluation of antidiabetic activity, diabetic Wistar rats were administered with 100, 200 and 300 mg/kg b.w. of VMFE. VMFE resulting into significant lowering of the levels of fasting blood glucose (p < 0.05) and increased of level of high-density lipoprotein-cholesterol (HDL-C), levels of total cholesterol (TC), triglyceride (TG) and low-density lipoprotein-cholesterol (LDL-C) were reduced significantly (p < 0.05). Therefore, this study provides scientific evidence for antidiabetic activities of V. mombassae fruits extracts, and validates its traditional use in the management of diabetes mellitus type 2.